Ethnobotany of The Tengger Community: A Case Study of Ngadas Village, Enclave Area of Bromo Tengger Semeru National Park - Hilwan, Iwan; Sabila, Siska Aisyah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
One of the natural conservation areas in East Java is the Bromo Tengger Semeru National Park (TNBTS). The research aims to carry out ethnobotanical studies in the framework of knowledge preservation. The research procedures included literature study, field observations, interviews, vegetation analysis, and data analysis. The results showed that the use of plants by the Tengger people of Ngadas Village was 69 species of plants. The use group consists of food and vegetable plants, medicinal plants, traditional and religious plants, plants for firewood, building materials, conservation and animal feed. The highest Importance Value Index for field plots for tree growth rate is owned by mountain cypress at 229.56% while forest plots for tree growth rate are owned by cinnamon at 39.95%. The highest Index of Cultural Significance is owned by rice originating from outside Tengger at 72. The Important Value Index of mountain cypress in the fields is 229.56% and the Index of Cultural Significance is 45. This shows the preservation of high mountain cypress when viewed from the INP value although the utilization of mountain cypress belongs to the very high category. Keywords: Bromo Tengger Semeru National Park, ethnobotany, Ngadas, Tengger